THE EFFECT OF VISUALIZATION, AUDITORY AND KINESTHETIC (VAK) MODEL TOWARD THE STUDENTS’ ABILITY IN WRITING PROCEDURE TEXT AT GRADE IX MTsN 1 REGENCY OF INDRAGIRI HULU - Maysa Witari, Destri Wahyuningsih (Menara Ilmu, 2019)
Abstract :The purpose of this research were to find out is there any significant effect of Visualization, Auditory and Kinesthetic (VAK) Model toward Writing Skill of Procedure Text at Great IX Mtsn 1 Regency of Indragiri Hulu. This is an Experimental research. The research was carried out in MTsN 1 Indragiri Hulu from September 20th 2018 at grade IX MTsN 1 Regency of Indragiri Hulu. The data collection techniques in this research are observation, test, and documentation. Technique sampling in this research is simple random sample technique. The samples of this research were class IX.4 (Experimental Class) and IX.6 (Control Class) of School at MTsN 1 Regency of Indragiri Hulu. Every class consisted of 30 students. The instrument used to collect the data is test (Pretest and Post test). The data analysis in this research is used t-test. Based on the calculating of t-test that the out put independent samples Test shows Equal Variances Assumed which can be seen from the number of the "t" test result of 20,754 with df = 59, the mean difference = 0.000 is the difference of Standard Error =1,94819. The difference in the use of Visualization, Auditory and Kinesthetic (VAK) Model is lowest = 44,33306 and the highest is 36,52036. If tobservation (t observation) = 20,754 compared to ttable is obtained the price of criticism "t" at a significant level of 5% = 2.04. It can be seen the price of tobservation> ttable which means. Ha is accepted and Ho is rejected. It means that there is a significant effect ont the students’ writing skill procedure text at grade IX MTsN 1 Regency of Indragiri Hulu was succesfull. Key words: Writing skill, Procedure text, VAK